The Synthesis of Coconut Methyl Ester Using Organic Catalytic Agents - Sofyan, Muhammad Ihsan; Ma’ruf, Muhammad; Hafizah, Mas Ayu Elita; Manaf, Azwar (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2023)
Biodiesel is one of the biomass materials or renewable energy, which is needed today to replace fuel from fossil energy, which can reduce global warming and has a high renewability cycle. Biodiesel is derived from plants, therefore it is also called biofuel. One type of biodiesel group is coconut methyl ester (CME), which is biodiesel obtained from coconut oil as a raw material. In this study, a synthesis of used coconut oil and methanol has been carried out with an organic catalyst based on coconut coir called the ASK catalyst. The results of transesterification have provided some important information, including: the yield is 15-19.5% after usage of the ASK catalyst consisting of amorphous phase and crystalline phase ClK0.8Na0.2, with the density and viscosity of products are 0.788-0.802 g/ml and 0.6-1 mm2/s. These results allow it to provide a distinctive advantage in its application.